2022
DOI: 10.1111/are.16147
|View full text |Cite
|
Sign up to set email alerts
|

Fermented soybean meal can partially replace fishmeal and improve the intestinal condition of goldfish juveniles reared in a biofloc system

Abstract: This study evaluated the effects of different dietary inclusion levels of fermented soybean meal (FSM) as replacement for fish meal and their effects on the productive performance and intestinal condition of goldfish (Carassius auratus) produced in biofloc (BFT) system. Five isoproteic (39.5% crude protein) and isoenergetic diets (4250 kcal kg −1 of crude energy) were formulated with FSM inclusion levels of 0%, 7%, 14%, 21% and 28% (0, 11, 22, 32 and 43 fish meal replacement). A total of 400 goldfish (0.25 ± 0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 103 publications
0
4
0
Order By: Relevance
“…During fermentation, digestive and antioxidant enzymes are produced by L. acidophilus [22,82,127], although their contribution to the host's condition is doubtful. Dietary inclusion of fermented ingredients may improve the activity of digestive [35] and antioxidant enzymes in fish [128], but changes in these activities are not always observed [82,102,129]. In this study, it is worth highlighting that enzymatic activity was not negatively affected by any treatment, even by the CPB diet, especially when considering that soybean meal may contain enzyme inhibitors that could have negatively affected the digestive process [130] and antioxidant response [131].…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…During fermentation, digestive and antioxidant enzymes are produced by L. acidophilus [22,82,127], although their contribution to the host's condition is doubtful. Dietary inclusion of fermented ingredients may improve the activity of digestive [35] and antioxidant enzymes in fish [128], but changes in these activities are not always observed [82,102,129]. In this study, it is worth highlighting that enzymatic activity was not negatively affected by any treatment, even by the CPB diet, especially when considering that soybean meal may contain enzyme inhibitors that could have negatively affected the digestive process [130] and antioxidant response [131].…”
Section: Discussionmentioning
confidence: 82%
“…Several studies have shown that the use of fermented protein sources with LAB has a positive result on fish growth performance and allows higher inclusions of plant-based protein in the diets [6,13,31,32]. Furthermore, fermented plant-based ingredients have been observed to enhance the antioxidant response [33,34], digestive enzymatic activity, gut condition, and intestinal microbiota [35][36][37][38]. On the other hand, few studies have evaluated the complete substitution of fishmeal with fermented ingredients in plant-based diets [14,39,40].…”
Section: Introductionmentioning
confidence: 99%
“…Samad et al also found that partially replacing FM with FSBM could reduce the feed conversion ratio and improve protein efficiency and digestive enzyme activities of spotted seabass [38]. Cunha et al found that the partial replacement of FM by FSBM could improve the digestive enzyme activity of goldfish (Carassius auratus) [39].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have realized that LAB use sugar as a growth factor to produce metabolites such as short-chain fatty acids (SCFAs) during fermentation, which play prebiotic functions. Some studies demonstrated that prebiotics or their metabolites may simulate intestinal villus development [41,42]. For instance, fermented soybean meal could promote the height of fish villus [43].…”
Section: Discussionmentioning
confidence: 99%